Inovasi dan Karakterisasi Fisikokimia Organoleptik Cookies Sagu dengan Penambahan Tepung Buah Pandan Tikar dan Pasta Buah Merah - Marina, Vivi; Sarungallo, Zita Letviany; Murtiningrum, Murtiningrum; Situngkir, Risma Uli; Ginting, Dewi Muliana Beru (Jurnal Agroteknologi, 2026)
An innovation to improve the nutrition and flavor of the sago cookies by adding pandan tikar fruit (Pandanus tectorius) flour and red fruit (Pandanus conoideus) paste. This study aims to innovate the production of sago cookies by adding pandan tikar fruit (PTF) flour and red fruit paste (RFP), and characterize. their physical properties, sensory attributes, proximate composition, and total carotenoid content. This study used an experimental method with a completely randomized design involving six treatments, namely the ratio between PTF flour, sago starch, RFP, and margarine: F0 (10%: 45%: 0%: 15%), F1 (10%: 45%: 5%: 10%), F2 (10%: 45%: 10%: 5%), F3 (5%: 50%: 10%: 5%), F4 (10%: 45%: 15%: 0%), and F5 (0%: 55%: 15%: 0%). The main ingredients for the cookies were a mixture of sago starch, PTF flour, and red fruit paste, along with supporting ingredients such as eggs, skim milk, maizena, margarine, and sugar. The results showed that increasing the concentration of red fruit paste by 5-15% increased the color intensity, expandability, and total carotenoid content, but decreased the intensity of aroma, taste, texture, and proximate content of the resulting sago cookies. Meanwhile, increasing the concentration of PTF flour by 5-10% reduced the expandability and total carotenoid content but increased the intensity of aroma, taste, and proximate content of the resulting sago cookies. The preferred sago cookie formulations by panelists were F0 (10% PTF flour) and F4 (5% PTF flour; 10% RFP). The F0 formula produced pale yellow cookies with a strong pandan aroma, sweet taste, crispy texture, and a proximate composition of 4.8% moisture, 1.63% ash, 20.67% fat, 3.03% protein, 74.67% carbohydrates, and 69.87 ppm carotenoids. In comparison, F4 cookies were reddish-orange with a milder pandan aroma, moderately sweet taste, similar texture, and higher nutritional value, containing 6.49% moisture, 1.40% ash, 19.97% fat, 3.12% protein, 75.51% carbohydrates, and 189.38 ppm carotenoids. Keywords: cookies, organoleptic, pandan tikar fruit flour, physicochemical, red fruit, sago